Effectiveness of interventions for treating apophysitis in children and adolescents: protocol for a systematic review and network meta-analysis - Stig L. Midtiby; Niels Wedderkopp; Rasmus T. Larsen; Anne-Marie Fiala Carlsen; Dimitris Mavridis; Ian Shrier (Chiropractic & Manual Therapies, 2018)
Abstract Background Overuse injuries are reported to be more common than acute trauma in children and adolescents, causing pain and reduced function. The most common is apophysitis - a traction injury to the apophysis in growing individuals. The duration of symptoms reported in the literature is between 6 weeks to 6 months or more. The objective of this systematic review and network meta-analysis is to compare the effectiveness and safety of all available treatments for any type of apophysitis in children and adolescents. Methods/Design We will conduct a systematic review to retrieve all relevant studies applying a comparative design. Searches will be made in the Cochrane CENTRAL, MEDLINE, EMBASE, CINAHL and SportDiscus databases and via reference searching. The efficacy of treatments will be compared with respect to the outcomes 1) time to pain-free activity and 2) risk of subsequent injury. Risk of bias assessment will be made using revised tool for assessing risk of bias in randomized trials for Randomized trials and Robins-I tool for non-randomized trials. We will explore if different treatment comparisons are sufficiently similar in terms of effect modifiers (transitivity assumption) with the aim to conduct network meta-analyses for randomized and non-randomized studies separately. A treatment hierarchy will be obtained using the surface under the cumulative ranking curve (SUCRA) and mean ranks, visualized using rankograms. We will use the CINeMA software to apply the modified version of Grades of Recommendation, Assessment, Development and Evaluation (GRADE), developed specifically to evaluate the quality of evidence in network meta-analysis. Discussion To date the comparative effects of interventions for apophysitis seem to rely mainly on expert opinion. We aim to identify all comparative treatment designs described in the literature and synthesize data when possible. We will use the estimated treatment effects between injury locations to provide guidance in managing apophysitis. Trial registration PROSPERO ID number: CRD42018083746.